Intraarticular Hyaluronic Acid Preparations for Knee Osteoarthritis: Are Some Better Than Others?. (December 2021) - Webner, David; Huang, Yili; Hummer, Charles D.
Objective: This literature review summarizes evidence on the safety and efficacy of intraarticular hyaluronic acid (IAHA) preparations approved in the United States for the treatment of osteoarthritis of the knee. Design: A systematic literature search was performed in PubMed, Ovid MEDLINE, and SCOPUS databases. Only studies in which clinical outcomes of individual IAHA preparations alone could be assessed when compared to placebo, no treatment, other standard knee osteoarthritis treatments, and IAHA head-to-head studies were selected. Results: One hundred nine articles meeting our inclusion criteria were identified, including 59 randomized and 50 observational studies. Hylan G-F 20 has been the most extensively studied preparation, with consistent results confirming efficacy in placebo-controlled studies. Efficacy is also consistently reported for Supartz, Monovisc, and Euflexxa, but not for Hyalgan, Orthovisc, and Durolane. In the head-to-head trials, high-molecular-weight (MW) Hylan G-F 20 was consistently superior to low MW sodium hyaluronate preparations (Hyalgan, Supartz) up to 20 weeks, whereas one study reported that Durolane was noninferior to Supartz. Head-to-head trials comparing high versus medium MW preparations all used Hylan G-F 20 as the high MW preparation. Of the IAHA preparations with strong evidence of efficacy in placebo-controlled studies, Euflexxa was found to be noninferior to Hylan G-F 20. There are no direct comparisons to Monovisc. One additional IAHA preparation (ie, Synovial), which has not been assessed in placebo-controlled studies, was also noninferior to Hylan G-F 20. Conclusion: IAHA efficacy varies widely across preparations. High-quality studies are required to assess and compare the safety and efficacy of IAHA preparations.